Desa wisata sebagai aset soft power Indonesia - Machya Astuti; Sri Issundari (Masyarakat, Kebudayaan dan Politik, 2016)
Tourism village plays significant role for strengthening Indonesia soft power. The experience of Daerah Istimewa Yogyakarta (DIY) province proves that the development of tourism villages contribute in promoting “the power” of Indonesia through art, culture, custom and food to international society. Tourism Villages that located at Sleman, Bantul, Gunungkidul, Kulonprogo and city of Yogyakarta (called as tourism kampong) succeeded in attracting foreigners to stay and live as villagers, enjoy villagers daily live and learn Javanese culture. The study was conducted by observation and interviews. Data were analyzed with descriptive qualitative techniques. Data categorized and given a qualitative analysis of narrative. This research showed that tourism village is a new kind of tourism object that produce a new close relationship between Indonesian people and foreigners, functioned as a tool to make foreigners love Indonesia, prolong their stay in Indonesia, and promote Indonesian culture when they come back to their country. DIY’s experience is a best practice for other provinces in Indonesia to develop and promote its own distinctive tradition and culture through tourism villages. Finally, this effort will contribute in supporting Indonesia soft power.